Equivalent strain in simple shear of metals - Beygelzimer, Y. (Физика и техника высоких давлений, 2015)
We show that simple shear and pure shear form two groups of transformations with different properties. The equivalent strain is viewed as an external control parameter of the deformation process at low homologous temperatures. The von Mises strain satisfies group-theoretic properties of both groups, supporting its use for measuring the equivalent strain. On the other hand, the Hencky strain does not satisfy the simple shear group properties, implying that it is not appropriate for measuring the equivalent strain in simple shear. The paper also proposes a hypothesis explaining the absence of metal hardening in large simple shear deformations. This hypothesis explains why excluding rotations as prescribed by the finite strain theory is not valid. Показано, що простий і чистий зсуви утворюють дві групи перетворень з різними властивостями. Розглянуто еквівалентну деформацію як керуючий параметр процесу деформування. Показано, що деформація Von Mises задовольняє груповим властивостями і простого, і чистого зсуву, в той час як деформація Hencky не задовольняє груповим властивостям простого зсуву. На основі цього зроблено висновок про непридатність деформації Hencky в якості еквівалентної деформації простого зсуву. Висловлено й обґрунтовано гіпотезу про причину відсутності зміцнення металів при простому зсуві великої величини, яка пояснює, чому коректне (у рамках механіки кінцевих деформацій) виключення повороту, що відповідний кінцевому зсуву, призводить до невірного результату. Показано, что простой и чистый сдвиги образуют две группы преобразований с разными свойствами. Рассмотрена эквивалентная деформация как управляющий параметр процесса деформирования. Показано, что деформация Von Mises удовлетворяет групповым свойствам и простого, и чистого сдвигов, в то время как деформация Hencky не удовлетворяет групповым свойствам простого сдвига. На основе этого сделан вывод о непригодности деформации Hencky в качестве меры эквивалентной деформации простого сдвига. Высказана и обоснована гипотеза о причине отсутствия упрочнения металлов при простом сдвиге большой величины, которая объясняет, почему корректное (в рамках механики конечных деформаций) исключение поворота, соответствующего конечному сдвигу, приводит к неверному результату.